Phylogeography and postglacial recolonization of Europe by Rhinolophus hipposideros: evidence from multiple genetic markers. Issue 15 (25th July 2013) - Dool, Serena E.; Puechmaille, Sébastien J.; Dietz, Christian; Juste, Javier; Ibáñez, Carlos; Hulva, Pavel; Roué, Stéphane G.; Petit, Eric J.; Jones, Gareth; Russo, Danilo; Toffoli, Roberto; Viglino, Andrea; et al.
Abstract: The demographic history of Rhinolophus hipposideros (lesser horseshoe bat) was reconstructed across its European, North African and Middle‐Eastern distribution prior to, during and following the most recent glaciations by generating and analysing a multimarker data set. This data set consisted of an X‐linked nuclear intron (Bgn; 543 bp), mitochondrial DNA (cytb‐tRNA‐control region; 1630 bp) and eight variable microsatellite loci for up to 373 individuals from 86 localities. Using this data set of diverse markers, it was possible to determine the species' demography at three temporal stages. Nuclear intron data revealed early colonization into Europe from the east, which pre‐dates the Quaternary glaciations. The mtDNA data supported multiple glacial refugia across the Mediterranean, the largest of which were found in the Ibero‐Maghreb region and an eastern location (Anatolia/Middle East)–that were used by R. hipposideros during the most recent glacial cycles. Finally, microsatellites provided the most recent information on these species' movements since the Last Glacial Maximum and suggested that lineages that had diverged into glacial refugia, such as in the Ibero‐Maghreb region, have remained isolated. These findings should be used to inform future conservation management strategies for R. hipposideros and show the power of using a multimarker data set for phylogeographic studies.